Effect of colchicine mutagen on phenotype and genotype of Vigna unguiculata var. sesquipedalis the 7th generation - F. FATHURRAHMAN; MARDALENI MARDALENI; AGUNG KRISIANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fathurrahman F, Mardaleni, Krisianto A. 2023. Title Effect of colchicine mutagen on phenotype and genotype of Vigna unguiculata var. Sesquipedalis the 7th generation. Biodiversitas 24: 1408-1416. The problem with long bean species is the low diversity of varieties, so obtaining them using chromosomal mutations was necessary. One of the ingredients used was colchicine. The aim of this study was to determine the effectiveness of the mutagen colchicine against mutations that occur in Vigna unguiculata var. sesquipedalis the 7th generation (renek long bean). The design used was a factorial Completely Randomized Design consisting of two factors. The first factor was four colchicine concentration levels: including without colchicine (the control) and colchicine concentration (0.01%, 0.05%, and 0.09%). The second factor was the soaking of the V. unguiculata var. sesquipedalis seeds, namely without soaking of seeds and soaking seeds (6, 12, 18, and 24 hours). Further phenotype analysis was tested statistically using the DMRT test at p < 0.05, while genotypes were analyzed using karyotypes and statistical T-test at p < 0.05. The results showed that treatment with 0.09% of colchicine and soaking for 24 hours was the best combination. Phenotype analysis showed increased growth with colchicine treatment: plant height increased by 20.59%, pod weight increased by 0.88%, the number of pods increased by 47.93%, pod length increased by 22.50%, and 100 seed weight increased by 15.91%. While Genotype analysis obtained a total of 11 karyotype chromosomes and 2n = 22 chromosomes. Chromosome karyotypes obtained two types, namely metacentric and telocentric. The arm length (p+q) in the 0.09% colchicine treatment sample and 24-hour soaking time was 1.77 µm longer than the control sample, which was 1.53 µm. It turns out that colchicine can increase the growth and changes in the structure of chromosomes so that a mutated V. unguiculata var. sesquipedalis species is obtained.